Pengaruh Budaya Organisasi terhadap kinerja pegawai PT. Restu Mahkota Karya Cikampek - Maulana, Ahmad; Chaerudin, Chaerudin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of organizational culture on employee performance at PT Restu Mahkota Karya Cikampek. This study uses a quantitative approach. Quantitative research aims to develop a mathematical model, where this research does not only use theories taken from the literature or theoretical studies, but is also very important to build hypotheses that have a relationship with the natural phenomena to be studied. Data collection techniques using a questionnaire and tested through a simple linear regression test, test the correlation coefficient and test the coefficient of determination. The results of this study indicate that the effect of organizational culture on performance is 37.3% and the remaining 62.7% is not examined in this study.